Following Germany's Lead: Using International Monetary Linkages to Estimate the Effect of Monetary Policy on the Economy - di Giovanni, Julian; McCrary, Justin; von Wachter, Till (The Review of Economics and Statistics, 2009)
Forward-looking behavior on the part of the monetary authority makes it difficult to estimate the effect of monetary policy interventions on output. We present instrumental variables estimates of the impact of interest rates on quarterly real output for several European countries, using German interest rates as the instrument. These estimates confirm a strong forward-looking bias in least squares estimates that persists even conditional on standard controls for the history of the system. Due to the potential for correlation of output shocks across countries, we interpret our estimates as lower bounds for the effect of monetary policy on real output.